Heterogeneous fog chemistry and S(IV) oxidation in the San Joaquin valley - Hoag, Katherine J., author; Collett, Jeffrey L., Jr., author (Colorado State University. Libraries, 1997)
Chemical and microphysical properties of winter radiation fogs present in the San Joaquin Valley (SJV) of California were measured during December 1995 and January 1996 as a part of the 1995 Integrated Monitoring Study (IMS95). The purpose of the study was to characterize winter particulate air quality problems often observed in this area. Stagnant conditions in the winter often lead to the formation of persistent and dense radiation fogs. These fogs act as processors of particulate matter through particle scavenging and removal in sedimenting fog drops and through particle production via chemical reactions that occur in the aqueous phase. The goal of the fog study portion of IMS95 was to gain more information about the fog drop chemistry as a function of drop size in an effort to more accurately determine the role of fogs in aerosol processing in this region. The major species measured in fogwater during this project were ammonium, nitrate, sulfate, acetate, formate and formaldehyde. The fogwater was also alkaline (median pH = 6.5) compared to a pH of 5.6 expected for atmospheric water in equilibrium with carbon dioxide. Droplet pH affects the amount of SO2 that is absorbed by the droplets and influences the relative importance of different S(IV) oxidation pathways. S(IV) oxidation by ozone was determined to be of primary importance (dominating 88 percent of the time in the southern SJV) because at the high pH values observed it becomes faster than S(IV) oxidation by hydrogen peroxide, which is more commonly investigated, and trace metal catalyzed autooxidation. High fog pH and abundant formaldehyde also led to significant formation of the S(IV) aldehyde complex hydroxymethanesulfonate (HMS). Size resolved fog drop collection revealed differences in fogwater chemical composition as a function of droplet size. In general, smaller drops were more acidic and more concentrated in ionic species than large drops. Calculations have been performed to determine the effect this chemical heterogeneity has on the roles fogs have in aerosol processing. Due to the nonlinearity of the ozone S(IV) oxidation rate, the acidity variations with drop size tend to enhance the oxidation. The observed S(IV) oxidation rates were 1.0 to 7.8 times faster than rates calculated using average fogwater acidity. Variations in other solute concentrations with drop size could affect the removal rates of these species from the air by deposition. Calculations assuming settling as the dominant deposition process estimate that using average fogwater composition of ionic species overestimates their removal rates by as much as a factor of 3.5.
December 1997.
Also issued as Katherine J. Hoag's thesis (M.S.) -- Colorado State University, 1998.
Keywords: Fog -- California -- San Joaquin Valley -- Measurement; Air quality -- California -- San Joaquin Valley -- Measurement; Air -- Pollution -- California -- San Joaquin Valley